Power Quality Analysis Of Grid-Connected Photovoltaic System With Adjustable Speed Drives - Muhammad Ikram, Mohd Rashid; Makbul, Anwari (2010)
This paper presents power quality analysis of a distributed generation system consisting of Photovoltaic (PV) – Inverter system as the renewable source connected to a network of Adjustable Speed Drives (ASDs) as the load. A small-scale laboratory consists of Photovoltaic, Inverter, ASDs and loads system was setup. Two power supplies from PV and grid were connected to two ASDs which powered two separate induction motors. Load of motor 1 was fixed while load of motor 2 was varied. In the experiment, both energy supplies from the grid and photovoltaic system were connected to the loads. Measurements have been done at both side of power transformer to analyze power quality in the system.